2004
DOI: 10.1074/jbc.m404689200
|View full text |Cite
|
Sign up to set email alerts
|

Combined Mutation of Catalytic Glutamate Residues in the Two Nucleotide Binding Domains of P-glycoprotein Generates a Conformation That Binds ATP and ADP Tightly

Abstract: Here we characterized this conformation using pure mouse MDR3 P-glycoprotein and natural MgATP and MgADP. Mutants E552A/E1197A, E552Q/E1197Q, E552D/ E1197D, and E552K/E1197K had low but real ATPase activity in the order Ala > Gln > Asp > Lys, emphasizing the requirement for Glu stereochemistry. Mutant E552A/ E1197A bound MgATP and MgADP (1 mol/mol) with K d 9.2 and 92 M, showed strong temperature sensitivity of MgATP binding and equal dissociation rates for MgATP and MgADP. With MgATP as the added ligand, 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
125
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 39 publications
15
125
0
Order By: Relevance
“…In human Pgp, the double mutant E556Q/E1201Q does not show steady state hydrolysis but can trap the nucleotide in the transition state (20), and the results were identical with equivalent mutations in mouse Pgp (22). Using crude membranes obtained from HeLa cells infected-transfected with mutant Pgp, we observed that 8-azido-[␣-32 P]ATP was occluded in a manner similar to the Vi-induced trapping in wild-type Pgp.…”
Section: The Mutant Pgp E556q/e1201q Exhibits Very Low Levels Of Atp mentioning
confidence: 62%
See 4 more Smart Citations
“…In human Pgp, the double mutant E556Q/E1201Q does not show steady state hydrolysis but can trap the nucleotide in the transition state (20), and the results were identical with equivalent mutations in mouse Pgp (22). Using crude membranes obtained from HeLa cells infected-transfected with mutant Pgp, we observed that 8-azido-[␣-32 P]ATP was occluded in a manner similar to the Vi-induced trapping in wild-type Pgp.…”
Section: The Mutant Pgp E556q/e1201q Exhibits Very Low Levels Of Atp mentioning
confidence: 62%
“…Formation of the Pgp⅐ATP (in the mutant Pgp) or Pgp⅐ADP⅐Vi (in the wild-type Pgp) reaction intermediates is a slow process that occurs over several minutes (20,22,30). Moreover, we show that in the temperature range 10 -34°C, the trapping reaction is linear for at least 5 min (e.g.…”
Section: Photocross-linking Of 8-azido[␣-32 P]atp Tomentioning
confidence: 65%
See 3 more Smart Citations